ChemInform Abstract: Lewis Acidity of Si6Cl12 and Its Role as Convenient SiCl2 Source. Issue 48 (December 2015) - Tillmann, Jan; Moxter, Maximilian; Bolte, Michael; Lerner, Hans‐Wolfram; Wagner, Matthias
Abstract: Crystals of the free cyclohexasilane Si6 Cl12 (I) are obtained by decomplexation of [Bu4 N]2 [Si6 Cl12 ]Cl2 using 2.5 equiv.